1994
DOI: 10.3758/bf03200771
|View full text |Cite
|
Sign up to set email alerts
|

The sequential view: From rapidly fading stimulus traces to the organization of memory and the abstract concept of number

Abstract: The development ofthe sequential approach to instrumentallearning from about 1958 to the present is described. The sequential model began as an attempt to explain a particular dass of neglected partial reward phenomena, those in which performance in acquisition and extinction is influenced by the particular sequence in which rewarded and nonrewarded trials occur in acquisition, and it was subsequently applied to a variety of other phenomena. Over time, the sequential model grew, sometimes through the replaceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

23
207
1
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(233 citation statements)
references
References 114 publications
(181 reference statements)
23
207
1
2
Order By: Relevance
“…Later, when the reinforced trials appear during reacquisition, their presence should help activate not only the excitatory context of acquisition but also the inhibitory association formed during extinction, causing a slower reacquisition than in a standard extinction condition where only the acquisition context is retrieved. Consistently with Capaldi's (1967Capaldi's ( , 1994 sequential learning theory, Ricker and Bouton (1996) suggested that reacquisition is controlled by a "trial-signaling" mechanism, whereby the animal learns that a certain type of trial, either a reinforced or a non-reinforced trial, reliably signals the type of upcoming trial. As a result, during acquisition animals not only learn that the cue is paired by the reinforcer, but also that reinforced trials follow other reinforced trials, whereas during standard extinction animals learnt that non-reinforced trials follow other non-reinforced trials.…”
mentioning
confidence: 90%
“…Later, when the reinforced trials appear during reacquisition, their presence should help activate not only the excitatory context of acquisition but also the inhibitory association formed during extinction, causing a slower reacquisition than in a standard extinction condition where only the acquisition context is retrieved. Consistently with Capaldi's (1967Capaldi's ( , 1994 sequential learning theory, Ricker and Bouton (1996) suggested that reacquisition is controlled by a "trial-signaling" mechanism, whereby the animal learns that a certain type of trial, either a reinforced or a non-reinforced trial, reliably signals the type of upcoming trial. As a result, during acquisition animals not only learn that the cue is paired by the reinforcer, but also that reinforced trials follow other reinforced trials, whereas during standard extinction animals learnt that non-reinforced trials follow other non-reinforced trials.…”
mentioning
confidence: 90%
“…As a concrete example, in Hull's (1943) the:' ory, the strength of the tendency to make such intratrial responses was said to increase when they were reinforced and to decrease when they were nonreinforced. The intratrial conception of the response, despite its general popularity, is difficult to reconcile with a wide variety ofempirical findings (see, e.g., Capaldi, 1992Capaldi, , 1994Capaldi, Miller, Alptekin, & Barry, 1990).…”
mentioning
confidence: 99%
“…For example, an animal may have received the series SNS' and PNS', or PNP' and SNP' (where S' and P' are twice the magnitude of Sand P). In these series, the memory of N could be strongly associated with an upcoming reward, and the memory of reward could be associated with N (Capaldi, 1994). Ordinal position could also be associated with reward outcomes because the first and third positions are always rewarded and the second position is never rewarded (Burns et aI., 1999).…”
mentioning
confidence: 99%
“…Though position learning is now emphasized (e.g., Henson, 1998) in human cognition, it began receiving attention (e.g., Bower, 1971 ;Ebenholtz, 1972) long after memoryassociation theories (e. g., Ebbinghaus, 1913) had developed rich traditions. The study of memories, usually of differing reward events, in animal serial learning also has a long history that has produced clear evidence for animals employing reward memories in serial problems; and the understanding of the nature of those memories is now fairly sophisticated (reviewed by Capaldi, 1994). Evidence that animals use information about the position of items in a list is recent, but also clear (Burns, Dunkman, & Detloff, 1999;Burns, Kinney, & Criddle, (2000) ; Burns, Wiley, & Payne, 1986;Chen, Swartz, & Terrace, 1997;Couvillon, Brandon, Woodard, & Bitterman, 1980; D 'Amato & Colombo, 1988, Roiblat, Pologue, & Scopatz, 1983Straub & Terrace, 1981).…”
mentioning
confidence: 99%
See 1 more Smart Citation